Property ownership and its implications for urban development The Case study (the development project of the Rashid camp for housing in Baghdad) - Atheeb Ali, Jalal; Khairi Othman, Areaj (Journal of Planner and Development, 2020)
Of the importance of the concept of ownership of real estate as the basic basis from which various projects are launched in various economic, tourism, and urban areas .... The need to research the diagnosis of real estate reality went astray in the difficulties, which played a decisive role in the process of urban development.  This leads us to the research problem of the difficulty of implementing urban development plans in many cases due to the absence of a clear methodology for organizing and modernizing the ownership of real estate and its coordination with the management of urban land and to achieve the objective of the research by seeking a methodology for a new proposed legal planning for the future ownership of real estate in the capital Baghdad To facilitate dealing with them and to limit the problems and obstacles to the development of urban areas related to the acquisition of real estate.  The concept of real estate ownership, legal classification and its relation to the management of urban land was clarified and clarified, from the theoretical side to the practical aspect. The research tackled the issues of ownership in the study area (Baghdad) and the methodology of regulating the real estate for the residential project based on field work. And finally, relying on the above, the hypothesis has been proven by the methodological work of a proposed new mechanism to acquire real estate to overcome its problems and facilitate the acquisition of real estate. One of the most important conclusions of the research is that the changing and multiple contexts of rights and property systems in the resources that follow urban growth and urbanization cause problems and slow the implementation of urban development plans due to the collision of ownership of real estate due to the lack of a clear methodology in dealing with them and organizing them. To facilitate the use of real estate and to create a comprehensive perspective on the acquisition of real estate (legal, institutional, regulatory, procedural).